Simplified Approaches for the Production of Monocyte-Derived Dendritic Cells and Study of Antigen Presentation in Bovine - Cunha, Patricia; Gilbert, Florence B.; Bodin, Jennifer; Godry, Lise; Germon, Pierre; Holbert, Sebastien; Martins, Rodrigo Prado (Frontiers in Veterinary Science, 2022)
Dendritic cells are sentinels of the immune system responsible for the initiation of adaptive immune mechanisms. In that respect, the study of these cells is essential for a full understanding of host response to infectious agents and vaccines. In ruminants, the large blood volume facilitates the isolation of abundant monocytes and their derivation to other antigen presenting cells such as dendritic cells and macrophages. However, the available protocols for the production of bovine monocytes-derived dendritic cells (moDC) rely mostly on time-consuming and costly techniques such density gradient separation and magnetic sorting of cells. In this study, we describe a simplified protocol for the production of bovine moDC using conventional and serum-free media. We also employ moDC produced by this approach to carry out a flow cytometry-based antigen presentation assay adapted to blood fresh or frozen cells. The experimental strategies described here might enable the setup of studies involving a large number of individuals, requiring a large number of dendritic cells or relying on the utilisation of cryopreserved blood cells. These simplified protocols might contribute to the elucidation of cell-mediated immune responses in bovine.